THE EFFECT OF SOCIAL INTERACTION OF THE FISHERMAN COMMUNITY ON THE STRATIFICATION OF COASTAL COMMUNITIES OF SABARU VILLAGE, LIUKANG TAGAYA DISTRICT, PANGKEP REGENCY - Arpandi Arpandi (UNM Geographic Journal, 2022)
This study aims to find out 1) The description of the social interaction of the fishing community in the coastal community of Sabaru Village, Liukang Tangaya District, Pangkep Regency 2) The description of the stratification of the coastal community of Sabaru Village, Liukang Tangaya District, Pangkep Regency. 3) The description of the social interaction of the fishing community towards the stratification of the Sabaru village community, Liukang Tangaya District, Pangkep. This study uses quantitative research with a population of 160 fishing communities. The results show that 1) The description of the social interaction of the fishermen community in the village of Sasusu, Liukang Tangaya District, Pangkep Regency is in the "good" category. Based on indicators, among others, a) Social Exchange, fishermen who live in groups can improve relations, b) Cooperation is a way for fishermen to catch fish more easily c) Competition, fellow fishermen try to maintain stability d) Conflicts that occur can be resolved. 2) The description of the stratification of coastal communities in the village of Sabatu, Liukang Tangaya sub-district, Pangkep Regency is in the "good" category. Based on indicators, among others, a) Objective distribution of privileges, catching fish together b) Household system, favorable ship conditions c) Criteria for conflicting systems, dominant fishing d) Symbols of position, not comparing e ) Does not differentiate position f) Solidarity among individuals or groups. 3) There is an influence that is classified as "low" between the social interaction of the fishing community on the stratification of the coastal community of the Sasusu Village, Liukang Tangaya Sub-district, Pangkep Regency